Recent Advancement in Current Challenges and Opportunities for Civil Engineers: “Expansive Soil Stabilization Using Fly Ash as Stabilizing Agent” - Yadav, Navin Kumar; Prajapati, Bipin; Mishra, Onkar Nath; Varshney, Lokesh (International Journal of Membrane Science and Technology, 2023)
Expansive soils are challenges for engineering applications in virgin state because of their shrink-swell nature with moisture variation. Numerous stabilizers and number of methods have been used to stabilize expansive soils as an effort to make them more practical for construction purposes. Searching for suitable stabilizers to overcome soil difficulties caused by the expansive nature of soil is the key issue, not only in terms of achieving the required soil engineering characteristics but also in terms of environmental and economic concerns. The purpose of this article was to assess the current trends, challenges, and opportunities of various admixtures utilized for expansive soil improvement, as well as their economic and environmental consequences. A critical use of various admixtures commonly as soil stabilizers, including marble waste powder, fly ash, eggshell powders, stone waste, and lime powder is conducted. Furthermore, this paper is also focused to analyze the offered stabilizers in terms of soil geotechnical properties and sustainability in the field application. Sustainable and eco- friendly challenges overcome by the various techniques used in geotechnical field. One of them expansive soil stabilization with fly ash. Main objective of this paper is that waste from thermal power plant utilized as stabilizing agent for expansive soil stabilization.